(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2023)
This paper examines the work of artist Sabrina Gschwandtner, whose recent series of 16mm and 35mm film quilts reproduce sequences from early women directors’ films and from orphaned textile-production documentaries and re-edits their narratives through spatial montage by sewing celluloid strips into traditional quilt patterns. Appropriated from film archives, each strip of film holds embedded within it a history of women’s labor, and through her sewing techniques, which call attention to the connection between film’s intermittent motion mechanism and the sewing machine, Gschwandtner patches women’s film histories back together. By considering the techniques of colorists and editors in early cinema as originating within handcrafting and ‘feminine’ labor, the traces of their hands at work form new histories through Gschwandtner’s quilts. In her artwork, the invisible contributions of these forgotten women become visible, foregrounding their tactile, intensive, and time-consuming labor. Gschwandtner’s film quilts also suggest that, rather than digital technology marking the death of cinema, it has just liberated the celluloid strip to be used and encountered in endless new ways.